Exploring influencing factors for the selection of mobile phone service providers: A structural equational modeling (SEM) approach on Malaysian consumers - Rahman, Sabbir; Haque, A. K. M. Ahasanul; Ahmad, Mohd Ismail Sayyed (Academic Journals, 2010)
The aim of this paper is to assess the factors that have played significant role to select telecommunication service providers. A survey instruments were employed on Malaysian mobile phone operator’s consumers’ included by demographic background, price, service quality, service availability and promotion. Data were collected from the consumers’ of three mobile phone operator’s from major cities in Malaysia. To determine the factors and examining their relationship of those factors towards the consumer’s perception in selecting an operator’s services. This research has applied exploratory factor analysis, confirmatory factor analysis and structural equation modeling for testing hypotheses. From the result it is revealed price or call rate is the most important factor followed by service quality, service availability and promotion. It is hoped that the findings of this study will assist the mobile phone industry of Malaysia in what they can produce in their services and how they want to promote their services as well. The findings of this study also assist mobile phone operator’s managers to invest their resources more efficiently, making changes to crucial quality attributes that elicit the consumer’s satisfaction level. However, the findings of this study may provide needed feedback and contribute to the improvement of players’ strategy and their marketing program. The study only included information of limited variables and from few cities in Malaysia with limited sample size. However, further research should be considered to gather more information regarding the brand image, corporate image, and customers’ satisfaction dimensions in context of the Malaysian mobile phone operators with larger sample.